Eliminating race-based mental health disparities : promoting equity and culturally responsive care across settings - Williams, Monnica T.; Rosen, Daniel C.; Kanter, Jonathan; Arredondo, Patricia (Context Press, an imprint of New Harbinger Publications, Inc., 2019)
In this edited volume, three leading experts in race, mental health, and contextual behavior science address the urgent problem of racial inequities and biases, which often prevent people of color from seeking mental health services--leading to poor outcomes if and when they do receive treatment. This critical and timely guide provides clinicians and educators with evidence-based recommendations for addressing inequities at multiple levels, as well as best practices for compassionately and effectively helping clients across a range of cultural groups and settings.
Keywords: African Americans -- Mental health services.; African Americans -- Mental health.; Discrimination in mental health services -- United States -- Prevention.; Health and race -- United States.; Mental health services.; Black or African American -- psychology; Mental Health Services; Race Factors; Noirs américains -- Services de santé mentale.; Noirs américains -- Santé mentale.; Santé et race -- États-Unis.; Services de santé mentale.; Psychiatry.; MEDICAL.; Social Psychology.; PSYCHOLOGY.; Discrimination & Race Relations.; SOCIAL SCIENCE.; Mental health services; African Americans -- Mental health; African Americans -- Mental health services; Health and race; United States